2013
DOI: 10.1080/10807039.2012.650577
|View full text |Cite
|
Sign up to set email alerts
|

The Weight of Evidence Does Not Support the Listing of Styrene as “Reasonably Anticipated to be a Human Carcinogen” in NTP's Twelfth Report on Carcinogens

Abstract: Styrene was listed as “reasonably anticipated to be a human carcinogen” in the twelfth edition of the National Toxicology Program's Report on Carcinogens based on what we contend are erroneous findings of limited evidence of carcinogenicity in humans, sufficient evidence of carcinogenicity in experimental animals, and supporting mechanistic data. The epidemiology studies show no consistent increased incidence of, or mortality from, any type of cancer. In animal studies, increased incidence rates of mostly beni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Similarly, it is not surprising that there is a lack of consistency in the tumorigenic potential noted in the NTP studies as compared to analogous tests conducted by others. 32,33 It is also not surprising that there is a serious challenge presented by a false-positive rate yet to be accurately quantitated.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, it is not surprising that there is a lack of consistency in the tumorigenic potential noted in the NTP studies as compared to analogous tests conducted by others. 32,33 It is also not surprising that there is a serious challenge presented by a false-positive rate yet to be accurately quantitated.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the QWoE approach has been expanded to assess confidence in potential modes-of-action (MoA) for adverse effects in animal testing, and to assess the human relevance of the best supported MoA (Dekant, 2019). QWoE includes a more detailed assessment of study quality as compared to other evaluation systems such as the Klimisch (Klimisch et al, 1997), SciRAP (Beronius et al, 2018), or general WoE-approaches (Rhomberg et al, 2013a ; 2013b). Moreover, properly designed QWoE may provide a more reliable assessment of the outcome of animal/human studies, the doses/concentrations applied, and the strength and relevance of effects with respect to the hypothesis tested.…”
Section: Quantitative Weight Of Evidencementioning
confidence: 99%
“…Agents are classified into four groups by the International Agency for Research on Cancer (IARC 2014) as follows (summarized in IARC Table II This grouping is evidence-based (DeSesso and Lavin 2001; Rhomberg et al 2013): the more evidence that is found indicating carcinogenicity, the higher the carcinogen level of a substance. These four groups show the uncertainty of hazard identification.…”
Section: Hazardous Agent Identificationmentioning
confidence: 99%